(untitled) (Altre Modernità, 2024)
The South American Gran Chaco is a territory that brings together a diversity of nations, including the Wichí-Weenhayek, whose lands are situated within Argentine and Bolivian jurisdictions. Based on the analysis of two novels that represent its world from the fictional construction of an endogenous point of view, Eisejuaz (1971) by the Argentine writer Sara Gallardo, and En el país del silencio (1987) by the Bolivian writer Jesús Urzagasti, the relationship of this Chaco culture with the territory it inhabits and with water will be considered, as a support of a language that exceeds the human sphere. To pursue this approach, the study draws on anthropological essays, ethnographic studies, and contributions from the ancestral cultural legacy. The novels introduce two conceptions of oral intellectual heritage: ancestral memory and telluric memory. These concepts reveal a profound care for life that predates the conclusions reached later on by literate cultures.)